2014
DOI: 10.4049/jimmunol.1401959
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory or Proinflammatory Effect of an Adenosine Receptor Agonist on the Th17 Autoimmune Response Is Inflammatory Environment–Dependent

Abstract: Adenosine is a key endogenous signaling molecule that regulates a wide range of physiological functions, including immune system function and inflammation. Studies have shown that adenosine receptor (AR) agonists can be either anti- or pro-inflammatory in immune responses and in inflammation, and the clarification of the mechanisms causing these opposing effects should provide a better guide for therapeutic intervention. While previous studies mostly examined the effects of AR agonists on Th1-type immune respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 50 publications
4
59
1
Order By: Relevance
“…We also showed that this effect is dependent on γδ T cell function, is significantly reduced in recipient mice with defective γδ T cell function (TCR-δ −/− mice), and is restored if the TCR-δ −/− recipient mice received an injection of γδ T cells before induction of EAU. A kinetic study in which recipient mice were treated during different disease phases confirmed our previous finding (15) that the outcome of AR-targeted treatment is not always consistent and that the effect of treatment can be either pro- or anti-inflammatory, depending upon the immune status of the recipient. The suppressive effect was seen when ADA was administered on day 8–14, shortly before disease expression, whereas disease was exacerbated if ADA was injected either before EAU induction or immediately after EAU expression.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…We also showed that this effect is dependent on γδ T cell function, is significantly reduced in recipient mice with defective γδ T cell function (TCR-δ −/− mice), and is restored if the TCR-δ −/− recipient mice received an injection of γδ T cells before induction of EAU. A kinetic study in which recipient mice were treated during different disease phases confirmed our previous finding (15) that the outcome of AR-targeted treatment is not always consistent and that the effect of treatment can be either pro- or anti-inflammatory, depending upon the immune status of the recipient. The suppressive effect was seen when ADA was administered on day 8–14, shortly before disease expression, whereas disease was exacerbated if ADA was injected either before EAU induction or immediately after EAU expression.…”
Section: Introductionsupporting
confidence: 79%
“…Exogenous ADA was initially used to treat immune deficiencies involving ADA dysfunction (4; 911), but subsequent studies showed enhanced ADA function was associated with increased incidence of autoimmune disease (4; 12) and that suppression of aberrant ADA activity by ADA inhibitors has an anti-inflammatory effect (13; 14). Our interest in the use of ADA to treat autoimmune disease started with our early observation that ligands of adenosine A2A receptors (A2ARs) or adenosine A2B receptors (A2BRs) enhance, rather than suppress, Th17 autoreactive T cell responses (1517). Since ADA counteracts the effects of adenosine (9; 18; 19), we wished to determine whether ADA could be used to suppress Th17-type autoimmune responses.…”
Section: Introductionmentioning
confidence: 99%
“…The inflammatory environment has a strong impact on the effect of activation of adenosine receptors in regulating immune cells. Previously reported data have shown that late activation of adenosine receptors contributes to increased Th17 responses in an experimental autoimmune uveitis model (27). In agreement with these findings, our results also showed activation of adenosine receptors in the IMQ-induced psoriasis model following the 12-day regimen, where the initiation of inflammation had already been established.…”
Section: Foxp3supporting
confidence: 93%
“…The net effect of increased extracellular adenosine however is dependent on pathology, adenosine concentrations, receptor expression and cross-talk with pathways mediated by ATP and other signaling molecules. Conflicting reports of whether adenosine is pro-or anti-inflammatory underscore the complexity of this molecule's role in mediating neuroinflammatory cascades (Liang et al, 2014). …”
Section: The Role Of Adenosine In Neuroinflammationmentioning
confidence: 99%